2013
DOI: 10.1371/journal.pone.0074040
|View full text |Cite
|
Sign up to set email alerts
|

Unique Structure and Dynamics of the EphA5 Ligand Binding Domain Mediate Its Binding Specificity as Revealed by X-ray Crystallography, NMR and MD Simulations

Abstract: The 16 EphA and EphB receptors represent the largest family of receptor tyrosine kinases, and their interactions with 9 ephrin-A and ephrin-B ligands initiate bidirectional signals controlling many physiological and pathological processes. Most interactions occur between receptor and ephrins of the same class, and only EphA4 can bind all A and B ephrins. To understand the structural and dynamic principles that enable Eph receptors to utilize the same jellyroll β-sandwich fold to bind ephrins, the VAPB-MSP doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 64 publications
(90 reference statements)
4
32
0
Order By: Relevance
“…Finally, results together reveal that protein dynamics also play a central role in enzymatic catalysis, and allosteric actions operate in all three proteases, as we previously characterized on the dynamics of the transmembrane Eph receptor on different time scales (Qin et al, 2012(Qin et al, , 2015Huan et al, 2013). Therefore, it is promising and feasible to discover/design molecules that allosterically inhibit three enzymes.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, results together reveal that protein dynamics also play a central role in enzymatic catalysis, and allosteric actions operate in all three proteases, as we previously characterized on the dynamics of the transmembrane Eph receptor on different time scales (Qin et al, 2012(Qin et al, , 2015Huan et al, 2013). Therefore, it is promising and feasible to discover/design molecules that allosterically inhibit three enzymes.…”
Section: Discussionmentioning
confidence: 74%
“…However, when starting from the open EphA4 conformation, the recognition process has a lower energy barrier than when starting from closed conformation. A new x-ray structure revealed that the high affinity ephrin-binding pocket of EphA5 has an open pocket in the unbound state, resembling that of other Eph receptors bound to ephrins [50]. …”
Section: Resultsmentioning
confidence: 99%
“…To assess conformational exchanges over µs-ms, 15 N transverse relaxation dispersion experiments were acquired on the P56S-MSP domain in H-DPC micelle, on a Bruker Avance 800 spectrometer with a constant time delay ( T CP = 50 ms) and a series of CPMG frequencies, ranging from 40 Hz, 80 Hz, 120 Hz (x2), 160 Hz, 200 Hz, 240 Hz, 320 Hz, 400 Hz, 480 Hz, 560 Hz, 640 Hz, 720 Hz, 800 Hz, and 960 Hz (×2 indicates repetition) as we previously performed 47, 48 . A reference spectrum without the CPMG block was acquired to calculate the effective transverse relaxation rate by the following equation:…”
Section: Methodsmentioning
confidence: 99%